SEXUAL EDUCATION THROUGH DOLLS TO STRENGTHEN PERSONAL SAFETY OF CHILDREN WITH HIV/AIDS AT LENTERA FOUNDATION SURAKARTA - Muti'ah Diniyati; Ayu Khoirotul Umaroh; Endang Setyaningsih (LPPM Univ. Ibn Khaldun Bogor, 2026)
Children with HIV/AIDS are a vulnerable group that needs to strengthen their understanding of personal safety from an early age due to limited knowledge and the risk of experiencing unsafe treatment. Situation analysis shows that personal safety education that is appropriate to the child's age and condition is still limited, so that children do not fully understand the limits of their personal body and how to protect themselves. These problems are the basis for the implementation of community service activities that aim to increase the understanding of personal safety of children with HIV/AIDS through education using puppet props. The activity was carried out at the Surakarta Lentera Foundation involving 15 children aged 6-12 years. The activity method includes pre-test, interactive education about personal body parts, safe and unsafe touch, and direct practice using puppet props, then ending with a post-test. The results of the activity showed an increase in the average score of children's understanding from 66.1% before the activity to 95.2% after the activity. In addition, children show the courage to tell stories and ask for help when they are in uncomfortable situations. This activity is complemented by the implementation of training of trainers for caregivers and the submission of educational manuals as an effort to sustain the program. It can be concluded that personal safety education based on doll props is effective, easy to accept, and feasible to apply to community service activities for other vulnerable children.